Cutting-Caving Ratio Optimization of Fully Mechanized Caving Mining with Large Mining Height of Extremely Thick Coal Seam. (7th October 2019) - Wang, Kai; Zhao, Tong; Yetilmezsoy, Kaan; Zhang, Xiaoqiang
Abstract : Serious rib spalling and low recovery rate problems caused by the poor top-coal caving property (TCCP) were investigated in fully mechanized caving mining with large mining height (FMCMLMH) of extremely thick coal seam. For this aim, theoretical calculation, numerical simulation, and engineering application were applied to study the reasonable cutting-caving ratio under the influence of different factors. The calculation formula of reasonable cutting height in FMCMLMH was obtained, and effective factors were determined. Moreover, F t (the top-coal yield failure coefficient) and F w (the coal wall yield failure coefficient) were defined, and each factor was fitted by using a linear regression equation. The minimum F t of fully fractured top coal was 0.6, and the main influencing factors were buried depth and Protodyakonov coefficient. The maximum F w of the stable coal wall was 1.5, and the main influencing factors were buried depth and cutting height. According to the relationship between coal wall stability and recovery rate, the relationship between coal seam strength and top-coal thickness at different cutting heights was obtained, and the mining zone was divided into four subzones. Engineering application showed that the optimal cutting height of Xiegou Coal Mine was 4 m, the cutting-caving ratio was 1 : 2.75, and the recovery rate could reach more than 85%, which was the most reasonable.